2021
DOI: 10.21037/apm-20-1850
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck posture influences masticatory muscle electromyographic amplitude in healthy subjects and patients with temporomandibular disorder: a preliminary study

Abstract: Background: Despite the association of masticatory function with head posture and mandible movement, the impact of head posture on masseter muscle electrical activity remains unclear. This study aimed to investigate the electrical activity of the anterior temporal, masseter, superior trapezius, and sternocleidomastoid muscles in temporomandibular disorder (TMD) patients in three different head positions and compare the findings with those for healthy subjects.Methods: The study included 16 TMD patients and 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Moreover, a signi cant correlation was observed between the craniocervical position, hyoid bone position, and vertical craniofacial morphology. These results are consistent with those of previous studies [3,7,17,19].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, a signi cant correlation was observed between the craniocervical position, hyoid bone position, and vertical craniofacial morphology. These results are consistent with those of previous studies [3,7,17,19].…”
Section: Discussionsupporting
confidence: 94%
“…When abnormal posture of head and neck takes place during active growth stage of patient, the normal development of craniofacial structure may be disrupted due to biomechanical and anatomical connection between neck muscles and craniofacial structure [1][2][3][4]. Moreover, according to the previous epidemiologic studies, patients suffering from neck disorders showed a higher percentage of craniomandibular disorders, which are often accompanied by malocclusion [5][6][7][8]. Therefore, a hypothesis that head and cervical posture correlates to malocclusion was put forward and widely reported in the field of orthodontics and orthopedics [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to what has already been described in the introduction, i.e., the use of sEMG for assessing muscle activity during physiological and parafunctional activities [ 6 ], it is also used in the diagnosis of temporomandibular joint and masticatory muscle function and treatment of the TMDs [ 7 , 8 , 9 , 10 ]. Studies on the influence of psychological [ 11 , 12 , 13 , 14 ] and physical state on changes in the bioelectrical activity of the masticatory muscles appear on the sEMG [ 15 , 16 , 17 , 18 ].…”
Section: Surface Electromyography In Dentistry—presentmentioning
confidence: 99%
“…In the field of dentistry, sEMG has become a valuable tool for assessing muscle bioelectrical activity during physiological and parafunctional activities [ 6 ], it is also used in the diagnosis of temporomandibular joint and masticatory muscle function and treatment of temporomandibular disorders (TMDs) [ 7 , 8 , 9 , 10 ]. Studies on the influence of psychological [ 11 , 12 , 13 , 14 ] and physical state on changes in the bioelectrical activity of the masticatory muscles appear on sEMG [ 15 , 16 , 17 , 18 ]. The usefulness of sEMG has also been demonstrated in orthodontics, primarily in the monitoring of therapy.…”
Section: Introductionmentioning
confidence: 99%